Artificial graphite and its manufacturing method, and secondary battery and power consumption device containing said artificial graphite
By optimizing artificial graphite materials with controlled surface roughness and manufacturing processes, the energy density and service life of secondary batteries are enhanced, addressing the limitations of conventional materials.
Patent Information
- Application Number
- JP2023502709
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-24
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2041-12-24
AI Technical Summary
Conventional artificial graphite materials fail to meet the requirements for high energy density and long service life in secondary batteries, limiting their performance and durability.
The development of artificial graphite materials with specific surface roughness, true density, volume average particle diameter, and graphitization degree, along with controlled manufacturing processes, enhances the bonding force between graphite and adhesive, reducing particle interaction and improving energy density and safety.
The optimized artificial graphite materials improve energy density and extend the service life of secondary batteries, enhancing their safety performance and stability.
Smart Images

Figure 0007603141000013 
Figure 0007603141000014 
Figure 0007603141000015
Abstract
Description
[Technical field]
[0001] The present application relates to the field of secondary battery technology, and more particularly to artificial graphite and a method for producing the same, as well as a secondary battery and a power consuming device including the artificial graphite as a negative electrode active material. [Background technology]
[0002] Secondary batteries are widely used due to their excellent characteristics such as high energy density, non-pollution, and long service life.
[0003] In secondary batteries, artificial graphite is widely used as a negative electrode active material, but conventional artificial graphite cannot fully meet the requirements for high energy density batteries and cannot meet the requirements for long service life. Therefore, it is necessary to provide a new artificial graphite material that can further improve the energy density and does not affect the battery life. Summary of the Invention [Problem to be solved by the invention]
[0004] The present application has been made in view of the above problems, and aims to provide artificial graphite capable of realizing high energy density and good service life, a method for producing the same, and a negative electrode plate produced using the artificial graphite as a negative electrode active material. Further, the present application aims to provide a secondary battery having high energy density and good service life, a battery module including the secondary battery, a battery pack, and a power consuming device. [Means for solving the problem]
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] In a first aspect, the present application provides an artificial graphite material A, which is a secondary particle, and has a surface roughness η A ,6≦η AIn some embodiments, the artificial graphite material A satisfies 7≦η A <= 10.
[0007] In some embodiments, the true density of the artificial graphite material A is ρ A ≧2.20g / cm 3 and optionally, ρ A ≧2.25g / cm 3 It is.
[0008] In some embodiments, the volume average particle size Dv50 of the artificial graphite material A A is Dv50 A ≧10μm, optionally, 12μm≦Dv50 A Meets ≦20μm.
[0009] In some embodiments, the specific surface area of the artificial graphite material A is 1.5-4.0, optionally 2.5-3.5.
[0010] In some embodiments, the tap density of the artificial graphite material A is 0.8-1.4, optionally 0.9-1.1.
[0011] In some embodiments, the graphitization degree of the artificial graphite material A is 92% or more, optionally 94%-97%.
[0012] In some embodiments, the gram capacity of the artificial graphite material A is greater than or equal to 340 mAh / g, optionally 350-360 mAh / g.
[0013] In a second aspect of the present application, there is provided an artificial graphite material B, which is a primary particle, and has a surface roughness η B 2.5≦η B Satisfy ≦5.
[0014] In some embodiments, the artificial graphite material B has a .eta. B Satisfying ≦4.
[0015] In some embodiments, the true density of the artificial graphite material B is ρ B ≧2.20g / cm 3 and optionally, ρ B ≧2.25g / cm 3 It is.
[0016] In some embodiments, the volume average particle size Dv50 of the artificial graphite material B B is Dv50 B ≦15μm, optionally, 5μm≦Dv50 B Meets ≦12μm.
[0017] In some embodiments, the specific surface area of the artificial graphite material B is 0.5-3.0, optionally 1.0-2.5.
[0018] In some embodiments, the tap density of the artificial graphite material B is 0.8-1.4, optionally 1.1-1.3.
[0019] In some embodiments, the graphitization degree of the artificial graphite material B is 91% or more, optionally 92%-94%.
[0020] In some embodiments, the gram capacity of the artificial graphite material B is greater than or equal to 340 mAh / g, optionally 340-350 mAh / g.
[0021] The third aspect of the present application provides a method for producing an artificial graphite material A, which comprises the steps of: A step (A1) of providing raw materials and crushing and shaping them; A step (A2) of carrying out granulation; A step (A3) of performing a graphitization treatment; and a step (A4) of performing a surface roughening treatment to obtain the artificial graphite material A. Here, the artificial graphite material A is a secondary particle, and the surface roughness η of the artificial graphite material A is A ,6≦η A <= 12.
[0022] Regarding the manufacturing method of the artificial graphite material A, in some embodiments, the surface roughness η of the secondary particles before the graphitization treatment is A is 4-6.
[0023] Regarding the method for producing the artificial graphite material A, in some embodiments, the surface roughening treatment is It involves putting the material into the Mechanofusion and processing it at a specific rotation speed. said specific rotation speed is 500-1000 r / m, optionally 600-800 r / m; The duration of said treatment is 3-60 minutes, optionally 5-20 minutes.
[0024] Regarding the method for producing the artificial graphite material A, in some embodiments, the surface roughening treatment is Put the material into the granulator and keep passing dry air through it. heating to a treatment temperature and carrying out treatment at said treatment temperature, said treatment temperature being 300-800° C., optionally 400-600° C.; The duration of said treatment is from 1 to 8 hours, optionally from 2 to 4 hours.
[0025] In a fourth aspect, the present invention provides a method for producing an artificial graphite material B, which comprises the steps of: A step (B1) of providing raw materials and crushing and shaping them; A step (B2) of performing a graphitization treatment; and a step (B3) of performing a surface roughening treatment to obtain the artificial graphite material B, Here, the artificial graphite material B is a primary particle, and the surface roughness η of the artificial graphite material B B 2.5≦η B Satisfy ≦5.
[0026] Regarding the method for producing the artificial graphite material B, in some embodiments, the surface roughness of the primary particles before the graphitization treatment is 1.5-3.
[0027] Regarding the method for producing the artificial graphite material B, in some embodiments, the surface roughening treatment is It involves putting the material into the Mechanofusion and processing it at a specific rotation speed. said specific rotation speed is 800-1000 r / m, optionally 850-950 r / m; The duration of said treatment is 20-60 minutes, optionally 30-50 minutes.
[0028] Regarding the method for producing the artificial graphite material B, in some embodiments, the surface roughening treatment is Put the material into the granulator and keep passing dry air through it. and heating to a treatment temperature and carrying out the treatment at said treatment temperature, said treatment temperature being 300-800°C, optionally 400-600°C.
[0029] The duration of said treatment is from 1 to 8 hours, optionally from 2 to 4 hours.
[0030] A fifth aspect of the present application provides a secondary battery, wherein the secondary battery includes a negative electrode plate, the negative electrode plate includes a negative electrode active material, and the negative electrode active material includes artificial graphite material A of the present application and / or artificial graphite material B of the present application, or includes artificial graphite material A and / or B prepared by the method according to the third aspect and / or the fourth aspect of the present application.
[0031] A sixth aspect of the present application provides a power consuming device including a secondary battery according to the fifth aspect of the present application. Effect of the Invention
[0032] In the secondary battery according to the present application, the negative electrode active material includes an artificial graphite material A and / or an artificial graphite material B, and preferably includes both an artificial graphite material A and an artificial graphite material B. By appropriately setting the surface roughness of the graphite as the artificial graphite material A and the artificial graphite material B of the present application, the bonding strength between the graphite and the adhesive can be improved, the force between the graphite particles can be improved, and the rebound at the moment of roll-out after cold pressing can be reduced, thereby improving the life span and safety performance of the secondary battery. In addition, the bonding strength between the graphite and the adhesive can be improved, and the force between the graphite particles can be improved, so that a higher energy density can be achieved. The battery module, the battery pack, and the power consumption device of the present application include the secondary battery according to the present application, and therefore have at least the same advantages as the secondary battery. [Brief description of the drawings]
[0033] In order to more clearly explain the technical solutions of the embodiments of the present application, the following briefly introduces the drawings that need to be used in the embodiments of the present application. It is obvious that the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on the drawings on the premise of paying creative efforts. [Figure 1] FIG. 1 is a schematic diagram of a secondary battery according to an embodiment of the present application. [Diagram 2] FIG. 1 is a schematic diagram of a battery module according to an embodiment of the present application. [Diagram 3] FIG. 1 is a schematic diagram of a battery pack according to an embodiment of the present application. [Figure 4] FIG. 4 is an exploded view of FIG. [Diagram 5] 1 is a schematic diagram of a power consuming device according to an embodiment of the present application; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0034] Hereinafter, with appropriate reference to the drawings, embodiments specifically disclosing the composite artificial graphite and its manufacturing method, secondary battery, battery module, battery pack, and power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of structures that are actually the same may be omitted. This is to avoid the following description becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.
[0035] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the extreme values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. However, if 1 and 2 are listed as minimum range values, and 3, 4 and 5 are listed as maximum range values, the ranges 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5 are all envisaged. In this application, unless otherwise specified, the numerical range "ab" represents a shorthand representation of any combination of real numbers from a to b, where a and b are both real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" have already been listed in this specification, and "0-5" is merely a shorthand for combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0036] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0037] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0038] Unless otherwise specified, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, the terms "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the ingredients listed.
[0039] In the description of this specification, it should be explained that unless otherwise specified, "more than" and "less than" are inclusive, and "multiple" in "one or more" means two or more.
[0040] Electric energy, being an economical, practical, clean, easy-to-control and convert energy form, is increasingly being applied to various power consuming devices. Secondary batteries have advantages such as high energy density, excellent portability, no memory effect, and environmental friendliness, and are therefore preferred as power sources for power consuming devices. When the negative electrode active material is formed using conventional natural graphite or artificial graphite, the energy density of the formed secondary battery is not high enough, and the high energy density requirement cannot be fully met, and the high requirement in terms of service life cannot be met. Therefore, how to further improve the energy density and further extend the service life of secondary batteries has become a focus in the secondary battery technical field.
[0041] As a result of intensive research, the inventors have found that when an artificial graphite material is made into secondary particles or primary particles, the surface roughness of this artificial graphite material is set to a specific value, and a negative electrode active material is manufactured using this artificial graphite material, it is advantageous for a secondary battery to maintain a high energy density, and is advantageous for improving the service life and safety performance of the secondary battery, as well as the battery module, battery pack and power consuming device including this secondary battery.
[0042] [Artificial graphite material A and its manufacturing method] In a first aspect, the present application provides an artificial graphite material A, which is a secondary particle, and has a surface roughness η A ,6≦η A ≦12, preferably 7≦η A ≦10. The appropriate surface roughness η of artificial graphite material A A can improve the bonding strength between the graphite and the adhesive, further improve the force between the graphite particles, and further reduce the bounce at the moment of roll-out after cold pressing, thereby improving the service life and safety performance of the secondary battery; can also improve the bonding strength between the graphite and the adhesive, further improve the force between the graphite particles, and further achieve a higher energy density.
[0043] In some embodiments, the true density of the artificial graphite material A of the present application is ρ A ≧2.20g / cm 3 and optionally, ρ A ≧2.25g / cm 3 The appropriate true density of the artificial graphite material A can provide a high gram capacity for itself, which is advantageous for improving the gram capacity of the composite artificial graphite, and can also suppress the occurrence of side reactions during cycling, thereby improving the life span and safety performance of the secondary battery.
[0044] In some embodiments, the volume average particle size Dv50 of the artificial graphite material A of the present application A is Dv50 A ≧10μm, optionally, 12μm≦Dv50 AThe artificial graphite material A has a suitable volume average particle size, which allows the artificial graphite material A to have a high gram capacity, and is advantageous in improving the gram capacity of the composite artificial graphite, and also in suppressing the occurrence of side reactions during cycling, thereby improving the service life and safety performance of the secondary battery.
[0045] In some embodiments, the specific surface area of the artificial graphite material A of the present application is 1.5-4.0, and optionally 2.5-3.5. If the specific surface area of the artificial graphite material A is too high, the surface reaction activity will be strong, and side reactions will easily occur during the cycle process, resulting in poor life performance. If the specific surface area of the artificial graphite material A is too low, the surface active sites will be few, resulting in poor power performance of the material.
[0046] In some embodiments, the tap density of the artificial graphite material A of the present application is 0.8-1.4, and optionally 0.9-1.1. If the tap density of the artificial graphite material A is low, the stability of the slurry is poor and processing is difficult. The upper limit of the tap density of the artificial graphite material A is not particularly limited, and may be set according to the degree that can be realized by the conventional method.
[0047] In some embodiments, the graphitization degree of the artificial graphite material A of the present application is 92% or more, optionally 94%-97%. If the graphitization degree of the artificial graphite material A is too low, the capacity will be low, and if the graphitization degree of the artificial graphite material A is too high, the layer spacing will be narrow and the cycle expansion will be large.
[0048] In some embodiments, the gram capacity of the artificial graphite material A of the present application is 340 mAh / g or more, optionally 350-360 mAh / g. The higher the appropriate gram capacity of the artificial graphite material A, the higher the energy mass density of the secondary battery containing it. The artificial graphite material A of the present application has a high gram capacity, and therefore the secondary battery of the present application has high energy density characteristics.
[0049] The third aspect of the present application provides a method for producing an artificial graphite material A, which comprises the steps of: A step (A1) of providing raw materials and crushing and shaping them; A step (A2) of carrying out granulation; A step (A3) of performing a graphitization treatment; and a step (A4) of performing a surface roughening treatment to obtain the artificial graphite material A. Here, the artificial graphite material A is a secondary particle, and the surface roughness η of the artificial graphite material A is A ,6≦η A <= 12.
[0050] In the present application, the raw material in step (A1) may be, for example, one or more of green coke and calcined coke, and preferably, the raw material includes one or more of needled green petroleum coke, non-needled green petroleum coke, needled coal-based green coke, non-needled coal-based green coke, calcined needle coke, and calcined petroleum coke.
[0051] In some embodiments, in step (A1), the raw material may be crushed using any of the equipment and methods known in the art, such as a jet mill, a mechanical mill, or a roll mill. In the crushing process, many undersized particles are often generated, and in some cases oversized particles may be present. Therefore, after crushing, a classification process may be performed as necessary to remove undersized particles and oversized particles in the powder after crushing. After classification, a particle product with a good particle size distribution can be obtained, which facilitates the subsequent shaping and / or granulation process. Classification may be performed using equipment and methods known in the art, such as a classification sieve, a gravity classifier, a centrifugal classifier, etc.
[0052] In some embodiments, in step (A1), equipment (e.g., a shaping machine or other shaping equipment) and methods known in the art may be adopted to perform a shaping process on the particle product after the crushing process in step (A1), for example, to grind the edge angles of the obtained particle product, thus facilitating subsequent operations and making the obtained product more stable.
[0053] In some embodiments, step (A2) may employ equipment known in the art, such as a granulator, to perform granulation. The granulator typically includes a stirring reactor and a module for controlling the temperature of the reactor. In addition, the volume average particle size of the product obtained by granulation may be controlled by adjusting process conditions such as the stirring rotation speed, heating rate, granulation temperature, and temperature drop rate in the granulation process. For example, in the present application, the granulation conditions may be set as follows: stirring rotation speed: 800 r / min-1500 r / min; heating rate: 8-15° C. / min; granulation temperature: 400° C.-650° C.; and granulation time: 6-10 hours.
[0054] In some embodiments, step (A3) includes performing a graphitization treatment. The graphitization treatment includes a high-temperature graphitization treatment and a low-temperature graphitization treatment. In some embodiments, according to actual specific requirements, one or two of the high-temperature graphitization treatment and the low-temperature graphitization treatment may be appropriately selected for the treatment, and the high-temperature graphitization treatment and / or the low-temperature graphitization treatment may be repeated multiple times.
[0055] The high-temperature graphitization treatment can obtain graphite with a suitable graphitization degree and graphite layer spacing. In some embodiments, the temperature of the high-temperature graphitization treatment performed in step (A3) can be 2800°C-3200°C, for example, 2900°C-3100°C, 3000°C-3200°C. The graphite produced at the appropriate graphitization temperature can obtain a suitable graphitization degree and graphite layer spacing, so that the composite artificial graphite can obtain high structural stability and gram capacity.
[0056] The low-temperature graphitization can also provide graphite with a suitable graphitization degree and graphite layer spacing. In some embodiments, the temperature of the low-temperature graphitization performed in step (A3) can be 2500°C-2700°C, for example, 2500°C-2600°C, 2600°C-2700°C. The graphite produced at the appropriate graphitization temperature can provide a suitable graphitization degree and graphite layer spacing, thereby allowing the composite artificial graphite to have high structural stability and gram capacity.
[0057] Regarding the manufacturing method of the artificial graphite material A, in some embodiments, the surface roughness η of the secondary particles before the graphitization treatment is A is 4-6.
[0058] In some embodiments, the surface roughening treatment in step (A4) includes a method mainly performed by a physical method (hereinafter referred to as "method 1A"), specifically, It involves putting the material into the Mechanofusion and processing it at a specific rotation speed. said specific rotation speed is 500-1000 r / m, optionally 600-800 r / m; The duration of said treatment is 3-60 minutes, optionally 5-20 minutes.
[0059] In some embodiments, the surface roughening treatment in step (A4) includes a method mainly performed by a chemical method (hereinafter referred to as "method 2A"), specifically, Put the material into the granulator and keep passing dry air through it. heating to a treatment temperature and performing treatment at said treatment temperature, said treatment temperature being 300-800° C., optionally 400-600° C.; The duration of said treatment is from 1 to 8 hours, optionally from 2 to 4 hours.
[0060] In some embodiments, the surface roughening treatment performed in step (A4) may adopt either one or two of the methods 1A and 2A, and the treatment of the method 1A and / or the method 2A may be repeated multiple times.
[0061] [Artificial graphite material B and its manufacturing method] In a second aspect of the present application, there is provided an artificial graphite material B, which is a primary particle, and has a surface roughness η B 2.5≦η B ≦5, and preferably has a surface roughness η B 3≦η B≦4. The appropriate surface roughness η of artificial graphite material B B can improve the bonding strength between the graphite and the adhesive, further improve the force between the graphite particles, and further reduce the bounce at the moment of roll-out after cold pressing, thereby improving the service life and safety performance of the secondary battery.In addition, the bonding strength between the graphite and the adhesive can be improved, further improving the force between the graphite particles, and achieving a higher energy density.
[0062] In some embodiments, the true density of the artificial graphite material B is ρ B ≧2.20g / cm 3 and optionally, ρ B ≧2.25g / cm 3 The appropriate true density of the artificial graphite material B can provide a high gram capacity by itself, which is advantageous for improving the gram capacity of the composite artificial graphite, and can also suppress the occurrence of side reactions during cycling, thereby improving the service life and safety performance of the secondary battery.
[0063] In some embodiments, the volume average particle size Dv50 of the artificial graphite material B B is Dv50 B ≦15μm, optionally, 5μm≦Dv50 B The appropriate volume average particle size of the artificial graphite material B can improve the gram capacity of the artificial graphite material B, and is also advantageous in improving the gram capacity of the composite artificial graphite, and can also suppress the occurrence of side reactions during cycling, thereby improving the service life and safety performance of the secondary battery.
[0064] In some embodiments, the specific surface area of the artificial graphite material B is 0.5-3.0, and optionally 1.0-2.5. If the specific surface area of the artificial graphite material B is too high, the surface reaction activity will be strong, and side reactions will easily occur during the cycle process, resulting in poor life performance. If the specific surface area of the artificial graphite material B is too low, the surface active sites will be few, resulting in poor power performance of the material.
[0065] In some embodiments, the tap density of the artificial graphite material B is 0.8-1.4, and optionally 1.1-1.3. If the tap density of the artificial graphite material B is low, the slurry is less stable and difficult to process. The upper limit of the tap density of the artificial graphite material B is not particularly limited, and may be set according to the degree that can be realized by the conventional method.
[0066] In some embodiments, the graphitization degree of the artificial graphite material B is 91% or more, optionally 92%-94%. If the graphitization degree of the artificial graphite material B is too low, the capacity will be low, and if the graphitization degree of the artificial graphite material B is too high, the layer spacing will be narrow and the cycle expansion will be large.
[0067] In some embodiments, the gram capacity of the artificial graphite material B is 340 mAh / g or more, optionally 340-350 mAh / g. The higher the appropriate gram capacity of the artificial graphite material B, the higher the energy mass density of the secondary battery containing it. The artificial graphite material B according to the present application has a high gram capacity, and therefore the secondary battery according to the present application has high energy density characteristics.
[0068] A fourth aspect of the present application provides a method for producing an artificial graphite material B, which comprises the steps of: A step (B1) of providing raw materials and crushing and shaping them; A step (B2) of performing a graphitization treatment; and a step (B3) of performing a surface roughening treatment to obtain the artificial graphite material B, Here, the artificial graphite material B is a primary particle, and the surface roughness η of the artificial graphite material B B 2.5≦η B Satisfy ≦5.
[0069] In the present application, the raw material of step (B1) may be, for example, one or more of green coke and calcined coke, and preferably, the raw material includes one or more of needled green petroleum coke, non-needled green petroleum coke, needled coal-based green coke, non-needled coal-based green coke, calcined needle coke, and calcined petroleum coke.
[0070] In some embodiments, in step (B1), the raw material may be crushed using any of the equipment and methods known in the art, such as a jet mill, a mechanical mill, or a roll mill. In the crushing process, many undersized particles are often generated, and in some cases oversized particles may be present. Therefore, after crushing, a classification process may be performed as necessary to remove undersized particles and oversized particles in the powder after crushing. After classification, a particle product with a good particle size distribution can be obtained, which facilitates the subsequent shaping and / or granulation process. Classification may be performed using equipment and methods known in the art, such as a classification sieve, a gravity classifier, a centrifugal classifier, etc.
[0071] In some embodiments, in step (B1), equipment (e.g., a shaping machine or other shaping equipment) and methods known in the art may be adopted to perform a shaping process on the particle product after the crushing process in step (B1), for example, to grind the edge angles of the obtained particle product, thus facilitating subsequent operations and making the obtained product more stable.
[0072] In some embodiments, step (B2) includes performing a graphitization treatment. The graphitization treatment includes a high-temperature graphitization treatment and a low-temperature graphitization treatment. In some embodiments, according to actual specific requirements, one or two of the high-temperature graphitization treatment and the low-temperature graphitization treatment may be appropriately selected for the treatment, and the high-temperature graphitization treatment and / or the low-temperature graphitization treatment may be repeated multiple times.
[0073] The high-temperature graphitization treatment can obtain graphite with a suitable graphitization degree and graphite layer spacing. In some embodiments, the temperature of the high-temperature graphitization treatment performed in step (B2) can be 2800°C-3200°C, for example, 2900°C-3100°C, 3000°C-3200°C. The graphite produced at the appropriate graphitization temperature can obtain a suitable graphitization degree and graphite layer spacing, so that the composite artificial graphite can obtain high structural stability and gram capacity.
[0074] The low-temperature graphitization process can also provide graphite with a suitable graphitization degree and graphite layer spacing. In some embodiments, the temperature of the low-temperature graphitization process carried out in step (B2) can be 2500°C-2700°C, for example, 2500°C-2600°C, 2600°C-2700°C. The graphite produced at the appropriate graphitization temperature can provide a suitable graphitization degree and graphite layer spacing, thereby allowing the composite artificial graphite to have high structural stability and gram capacity.
[0075] Regarding the method for producing artificial graphite material B, in some embodiments, (B2) the surface roughness of the primary particles before the graphitization treatment is 1.5-3.
[0076] In some embodiments, the artificial graphite material B is obtained by performing a surface roughening treatment in step (B3).
[0077] In some embodiments, the surface roughening treatment in step (B3) includes a method mainly performed by a physical method (hereinafter referred to as "method 1B"), specifically, It involves putting the material into the Mechanofusion and processing it at a specific rotation speed. said specific rotation speed is 800-1000 r / m, optionally 850-950 r / m; The duration of said treatment is 20-60 minutes, optionally 30-50 minutes.
[0078] In some embodiments, the surface roughening treatment in step (B3) includes a method mainly performed by a chemical method (hereinafter referred to as "method 2B"), specifically, Put the material into the granulator and keep passing dry air through it. heating to a treatment temperature and carrying out treatment at said treatment temperature, said treatment temperature being 300-800° C., optionally 400-600° C.; The duration of said treatment is from 1 to 8 hours, optionally from 2 to 4 hours.
[0079] In some embodiments, the surface roughening treatment performed in step (B3) may adopt either one or two of the methods 1B and 2B, and the treatment of the method 1B and / or the method 2B may be repeated multiple times.
[0080] [Parameter measurement of artificial graphite materials A and B] In the examples and comparative examples of this application, the surface roughness η of the artificial graphite materials A and B A , η B Both can be calculated by the following method.
[0081]
number
[0082] where SSA is the specific surface area of the artificial graphite material, ρ is the true density of the artificial graphite material, and D k and V k may be read directly from the test data from the laser particle size analyzer (Malvern Master Size 3000) of the test equipment, where n represents the number of particle size intervals of the material, and n may be according to the settings of the laser particle size analyzer (e.g., n=80). Here, D k represents the average grain size of a certain grain size range of the material (i.e.: (upper grain size limit + lower grain size limit) / 2), and V k represents the volume ratio of particles in this interval among all particles.
[0083] In the examples and comparative examples of this application, the true densities ρ A , ρ B The density is measured using a true density measuring instrument (AccuPyc) in accordance with the standard GB / T 24586-2009.
[0084] In the examples and comparative examples of this application, the volume average particle diameter Dv50 of artificial graphite materials A and B A , Dv50 B , refer to standard GB / T 19077.1-2016 and measure using a laser particle size analyzer (e.g. Malvern Master Size 3000).
[0085] Here, Dv50 A , Dv50 B The physical definition of is as follows:
[0086] Dv50 A , Dv50 B : The particle size corresponding to when the cumulative volume distribution percentage of the artificial graphite material reaches 50%.
[0087] In the examples and comparative examples of the present application, the specific surface area of the artificial graphite materials A and B is tested by the nitrogen gas adsorption specific surface area analysis test method in accordance with GB / T 19587-2017, and calculated by the BET (Brunauer Emmett Teller) method, where the nitrogen gas adsorption specific surface area analysis test may be performed by a Tri-Star 3020 type specific surface area pore size analyzer manufactured by Micromeritics, USA.
[0088] In the examples and comparative examples of the present application, the tap density of the artificial graphite materials A and B is measured with a powder tap density tester (such as Dandong Bettersize BT-301) in accordance with the GB / T 5162-2006 standard.
[0089] In the examples and comparative examples of this application, the powder compaction density of artificial graphite materials A and B is tested by referring to GB / T 24533-2009 and using an electronic pressure tester (such as UTM7305). A certain amount M of powder sample to be tested is placed in a special compaction mold (bottom area S), different pressures are set, the pressure is kept for 30 s, the pressure is released, and waiting for 10 s, and the thickness H of the powder after compaction at this pressure is read from the instrument, and the compaction density at this pressure can be calculated, where the compaction density of the negative electrode active material at this pressure=M / (H×S).
[0090] Graphite layer spacing d 002 The graphitization degree may be tested by adopting a method known in the art. For example, the graphitization degree may be tested using an X-ray diffraction device (e.g., Bruker D8 Discover), and the test may be performed according to JIS K 0131-1996, JB / T 4220-2011, 002 Measure the size of and calculate the formula G = (0.344-d 002 The degree of graphitization may be calculated based on d / (0.344-0.3354), where d 002 is the layer spacing in the artificial graphite crystal structure expressed in nanometers (nm).
[0091] The gram capacities of the artificial graphite materials A and B are measured by using methods known in the art, for example, as follows.
[0092] <Method of measuring gram volume> The prepared artificial graphite material, conductive agent Super P, thickener (CMC-Na), adhesive (SBR) are uniformly mixed with solvent deionized water according to a mass ratio of 94.5:1.5:1.5:2.5 to prepare a slurry, which is coated on a copper foil current collector and dried in an oven for use. A lithium metal sheet is used as the counter electrode, a polyethylene (PE) film is used as the separator, and ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed according to a volume ratio of 1:1:1. Then, LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte, where the concentration of LiPF6 is 1mol / L. The above parts are assembled into a CR2430 type coin battery in a glove box protected by argon gas.
[0093] The resulting coin battery was left to stand for 12 hours, then discharged to 0.005 V at a current of 0.05 C, left to stand for 10 minutes, discharged to 0.005 V at a current of 10 μA, and charged to 2 V at a current of 0.1 C, and the charge capacity was recorded. The ratio of the charge capacity to the mass of the composite artificial graphite is the gram capacity of the artificial graphite material produced.
[0094] [Secondary battery] In a fifth aspect of the present application, there is provided a secondary battery, which comprises any one of the artificial graphite materials A according to the first aspect of the present invention and / or any one of the artificial graphite materials B according to the second aspect of the present invention.
[0095] An embodiment of the present application provides a secondary battery. Generally, the secondary battery includes a positive electrode plate, a negative electrode plate, an electrolyte, and a separator. During charging and discharging of the battery, active ions shuttle between the positive electrode plate and the negative electrode plate to store and release ions. The electrolyte serves to conduct ions between the positive electrode plate and the negative electrode plate. The separator is disposed between the positive electrode plate and the negative electrode plate, and serves mainly to prevent short circuit between the positive and negative electrodes, while allowing ions to pass through.
[0096] [Negative electrode plate] The negative electrode plate includes a negative electrode current collector and a negative electrode film disposed on at least one surface of the negative electrode current collector. For example, the negative electrode current collector has two surfaces facing each other in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on either one or both of the two facing surfaces of the negative electrode current collector.
[0097] The negative electrode current collector may be made of a material having good electrical conductivity and mechanical strength, and may serve as a conductor and a current collector. In some embodiments, the negative electrode current collector may be made of copper foil.
[0098] The negative electrode film includes a negative electrode active material, the negative electrode active material including any one of the artificial graphite materials A according to the first aspect of the present application and / or any one of the artificial graphite materials B according to the second aspect of the present application, which can significantly reduce the rebound at the moment of roll-out after cold pressing in the manufacturing process of the negative electrode plate including the artificial graphite material of the present application, and can effectively improve the service life and safety performance of the secondary battery.
[0099] In some embodiments, the step of manufacturing a negative electrode plate by adopting any one or more artificial graphite materials of the present application may include dispersing a negative electrode active material including any one or more artificial graphite materials A and / or B of the present application, an adhesive, and an optional thickener and conductive agent in a solvent (the solvent may be deionized water) to form a uniform negative electrode slurry; and coating the negative electrode slurry on a negative electrode current collector, and obtaining a negative electrode plate after processes such as drying and cold pressing.
[0100] In some embodiments, the negative plate further optionally includes other negative active materials that can be used in secondary battery negative electrodes, which can be one or more of other graphite materials (e.g., other artificial graphites in this application, different from natural graphite), mesocarbon microbeads (abbreviated as MCMB), hard carbon, soft carbon, silicon-based materials, and tin-based materials.
[0101] In some embodiments, the adhesive may be selected from one or more of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyethylene alcohol (PVA), styrene butadiene rubber (SBR), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0102] In some examples, the viscosity increasing agent may be sodium carboxymethylcellulose (CMC-Na).
[0103] In some embodiments, the conductive agent used in the negative plate may be selected from one or more of graphite, superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0104] [Positive electrode plate] The positive electrode plate includes a positive electrode current collector and a positive electrode film that is disposed on at least one surface of the positive electrode current collector and includes a positive electrode active material. For example, the positive electrode current collector has two surfaces that face each other in the thickness direction of the positive electrode current collector, and the positive electrode film layer is disposed on either one or both of the two facing surfaces of the positive electrode current collector.
[0105] The positive electrode current collector may be made of a material having good electrical conductivity and mechanical strength, and in some embodiments, may be made of aluminum foil.
[0106] The present application is not limited to a specific type of positive electrode active material, and any material that can be used for the positive electrode of a secondary battery known in the art may be adopted, and those skilled in the art can select it according to actual needs.
[0107] In some embodiments, the secondary battery may be a lithium-ion secondary battery. The positive electrode active material may be selected from lithium transition metal oxides and their modifying materials, and the modifying materials may perform doping modification and / or coating modification on the lithium transition metal oxides. For example, the lithium transition metal oxide may be selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-containing phosphates with an olivine structure.
[0108] For example, the positive electrode active material of a secondary battery is LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 It may be selected from one or more of O2, LiFePO4 (LFP) and LiMnPO4.
[0109] In some embodiments, the positive electrode membrane may further include an adhesive. There is no limitation on the type of adhesive, and those skilled in the art may select it according to actual needs. For example, the adhesive used in the positive electrode membrane may include one or more of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE). In some embodiments, the positive electrode film further includes a conductive agent. The type of the conductive agent is not limited, and a person skilled in the art can select it according to actual needs. For example, the conductive agent used in the positive electrode film may include one or more of graphite, superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0110] [Electrolyte] The electrolyte serves to conduct ions between the positive and negative electrodes. The present application is not specifically limited to the type of electrolyte, and may be selected according to need. For example, the electrolyte may be liquid, gel, or all solid.
[0111] In some embodiments, the electrolyte is an electrolytic solution that includes an electrolyte salt and a solvent.
[0112] In some embodiments, the electrolyte salt may be selected from one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonate), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluoro(oxalato)borate), LiBOB (lithium bis(oxalato)borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalato)phosphate), and LiTFOP (lithium tetrafluoro(oxalato)phosphate).
[0113] In some examples, the solvent may be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), and diethyl sulfone (ESE).
[0114] In some embodiments, the electrolyte solution further optionally includes additives, for example, the additives may include anode film-forming additives, cathode film-forming additives, and additives that can improve some performance of the battery, such as additives that improve the overcharge performance of the battery, additives that improve the high temperature performance of the battery, and additives that improve the low temperature performance of the battery.
[0115] [Separator] A separator is further included in secondary batteries using liquid electrolyte and some secondary batteries using solid electrolyte. The separator is disposed between the positive electrode plate and the negative electrode plate and plays a role of isolation. The present application is not particularly limited to the type of separator, and any known porous structure separator with good chemical stability and mechanical stability may be selected and used. In some embodiments, the material of the separator may be selected from one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer may be the same or different.
[0116] [Exterior body] In some embodiments, the secondary battery may include an exterior body for packaging the positive electrode plate, the negative electrode plate, and the electrolyte. For example, the positive electrode plate, the negative electrode plate, and the separator may be stacked or wound to form a stacked structure battery core or a wound structure battery core, and the battery core is packaged in the exterior body, and an electrolyte may be adopted as the electrolyte, and the electrolyte is impregnated into the battery core. The number of battery cores in the secondary battery may be one or several, and can be adjusted according to demand.
[0117] In some embodiments, the exterior body of the secondary battery may be a soft bag, for example, a pouch-type soft bag. The material of the soft bag may be plastic, for example, may include one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc. The exterior body of the secondary battery may be a hard case, for example, an aluminum case, etc.
[0118] In some embodiments, the positive plate, the negative plate, and the separator may be fabricated into an electrode assembly by a winding process or a stacking process.
[0119] The present application is not particularly limited to the shape of the secondary battery, which may be cylindrical, rectangular or any other shape. Figure 1 shows a secondary battery 5 with a rectangular structure as an example.
[0120] [Battery module] In a sixth aspect of the present application, the secondary battery can be assembled into a battery module, and the number of secondary batteries included in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0121] Fig. 2 shows an example of a battery module 4. Referring to Fig. 2, in the battery module 4, the multiple secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by fasteners.
[0122] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.
[0123] [Battery pack] In a sixth aspect of the present application, the battery modules of the present application can be assembled into a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0124] 3 and 4 show an example of a battery pack 1. Referring to FIG. 3 and FIG. 4, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box may include an upper housing 2 and a lower housing 3, and the upper housing 2 is covered by the lower housing 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0125] [Power consumption equipment] A sixth aspect of the present application further provides a power consuming device, the power consuming device including the secondary battery of the present application, the secondary battery providing a power source for the power consuming device, the power consuming device may be, but is not limited to, a mobile device (such as a mobile phone, a laptop, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.
[0126] The power consumption device can select a secondary battery, a battery module or a battery pack according to its usage demand.
[0127] 5 shows an example power consuming device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module may be employed to meet the demand for high power and high energy density of the secondary battery of the power consuming device.
[0128] As another example, the power consuming device may be a mobile phone, a tablet computer, a notebook computer, etc. These power consuming devices are generally required to be thin, and may employ a secondary battery as a power source. EXAMPLES
[0129] The following describes examples of the present application. The examples described below are illustrative and are used only to interpret the present application, and should not be understood as limiting the present application. In the examples, specific techniques or conditions are not specified, but are carried out according to techniques or conditions described in the literature in the field or product instructions. Reagents or equipment used that do not specify the manufacturer are all common products that can be purchased commercially.
[0130] Example 1a Manufacturing of artificial graphite material A: (A1): The calcined needle coke raw material is crushed using a roll mill, and classified and shaped using a centrifuge and a shaping machine to obtain precursor 1; (A2): The precursor 1 obtained in step (A1) is subjected to a granulation process to obtain an intermediate 1, and an adhesive is added in the granulation process, and the amount of the adhesive used is 15% of the weight of the precursor 1 in the granulation step (A2). The granulation is performed using a granulator, and the stirring rotation speed is 1000 r / min, the heating rate is 10° C. / min, the granulation temperature is 650° C., and the granulation time is 8 hours. (A3): The intermediate 1 obtained in step (A2) is subjected to a graphitization treatment at a temperature of 3000°C; (A4): The product obtained in step (A3) is placed in a granulator, dried air is continuously passed through, the temperature is raised to 550°C at 5°C / min, and the temperature is maintained for 2 hours to obtain artificial graphite material A. This artificial graphite material A is a secondary particle, and has a surface roughness of 8.5.
[0131] Negative electrode plate manufacturing The artificial graphite material A, the conductive agent Super P, the adhesive SBR, and the thickener CMC-Na are mixed in a mass ratio of 96.2:0.8:1.8:1.2, and then thoroughly stirred in an appropriate amount of deionized water to form a uniform negative electrode slurry. The negative electrode slurry is coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing (the cold pressing pressure is 70 tons, and the cold pressing speed is 35 m / s), a negative electrode plate is obtained. The surface density of the negative electrode film layer is 10.7 mg / cm. 2 The compaction density of the negative electrode film layer is 1.71 g / cm 3 It is.
[0132] Positive electrode plate manufacturing Cathode active material LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), conductive agent (Super P), and adhesive PVDF are mixed in a weight ratio of 96.2:2.7:1.1 with an appropriate amount of NMP and thoroughly stirred to form a homogeneous positive electrode slurry. The positive electrode slurry is coated on the surface of a positive electrode current collector aluminum foil, and then dried and cold pressed to obtain a positive electrode plate. The compaction density of the positive electrode plate is 3.45 g / cm. 3 and the surface density is 18.8 mg / cm 2 It is.
[0133] Electrolyte production Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed according to a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte, where the concentration of LiPF6 is 1 mol / L.
[0134] Separator Polyethylene (PE) film is used.
[0135] Secondary battery manufacturing A positive electrode plate, a separator, and a negative electrode plate are stacked in that order and wound to obtain an electrode assembly. The electrode assembly is then placed in an outer casing, the above-mentioned electrolyte is added, and the secondary battery is obtained through processes such as packaging, standing, chemical formation, and degradation.
[0136] Examples 2a-17a and Comparative Examples 1a-2a Examples 2a-17a and Comparative Examples 1a-2a are basically the same as Example 1a, and the only differences are those shown in Tables 1-3. For Examples 2a-17a and Comparative Examples 1a-2a, unless otherwise specified in Tables 1-3, it indicates that they are the same as Example 1a.
[0137] The test results of the artificial graphite materials obtained in each of Examples 1a to 13a and Comparative Examples 1a to 5a are shown in Tables 1 to 3 below.
[0138] In Table 1, the processing method of step (A4) being "chemical" indicates that step (A4) is carried out by placing the material in a granulation tank, continuously passing dry air through it, raising the temperature to a predetermined processing temperature at a rate of 5°C / min, and maintaining the temperature at that processing temperature for a predetermined period of time. The processing temperature and processing time (i.e., maintenance time) are as shown in Table 1.
[0139] In Table 1, the processing method of step (A4) being “physical” means that (A4) is carried out by putting the material into the mechanofusion and processing it at a predetermined rotation speed, and the rotation speed and processing time are as shown in Table 1.
[0140] <Performance test> (1) The method for measuring the compaction density after cold pressing of the negative electrode film layer is as follows.
[0141] The negative electrode plates of the above examples and comparative examples were taken and cut into wafers with a small area S1 (unit of area S1: cm 2) and weigh it, recording it as M1 (unit of M1: g).
[0142] Measurement of the thickness of the negative electrode film (here, it is sufficient to measure the thickness of the negative electrode film layer on any one surface of the negative electrode current collector, thickness unit: cm) Wipe off the negative electrode film of the negative electrode plate after the above weighing, and weigh the negative electrode current collector and record it as M0 (unit of M0: g). If the negative electrode film is installed on only one surface of the negative electrode current collector, the weight of the negative electrode film = M1-M0, and if the negative electrode film is installed on both surfaces of the negative electrode current collector, the weight of the negative electrode film = (M1-M0) / 2.
[0143] The surface density of the negative electrode film=weight of the negative electrode film / S1.
[0144] Based on the "area density of the negative electrode film" and the "thickness of the negative electrode film", the "compact density after cold pressing of the negative electrode film" is calculated using the following formula, and the result is recorded in each of the tables below.
[0145] The compaction density of the negative electrode film after cold pressing=area density of the negative electrode film / thickness of the negative electrode film.
[0146] (2) The method for measuring the compaction density and cycle expansion rate of the negative electrode membrane after cycling is as follows.
[0147] The secondary batteries prepared in each embodiment and comparative example are charged at a constant current of 1C to a charge cut-off voltage of 4.2V, then charged at a constant voltage of ≦0.05C, left to stand for 5 minutes, and then discharged at a constant current of 1C to a discharge cut-off voltage of 2.8V, left to stand for 5 minutes, which is one charge-discharge cycle. In this manner, the batteries are subjected to 600 cycles of charge-discharge testing, and the negative electrode plate is disassembled and tested according to the method steps shown in 1 above, and the obtained "compact density of the negative electrode film after cycling" is recorded in each table below.
[0148] Based on the "compacted density of the negative electrode membrane after cold pressing" and the "compacted density of the negative electrode membrane after cycling", calculate the "cycle expansion rate of the negative electrode membrane (600 cys)" using the following formula and record it in each table below.
[0149] Cyclic expansion rate of negative electrode film (600cys) = (density of negative electrode film after cold pressing / density of negative electrode film after cycling - 1) x 100% Here, the compaction density after cold pressing of the negative electrode film is the result of the above-mentioned Method 1 test.
[0150] [Table 1]
[0151] [Table 2]
[0152] [Table 3]
[0153] Example 1b Manufacturing of artificial graphite material B: (B1): Crush raw petroleum coke using a mechanical mill, classify and shape the raw petroleum coke using a centrifuge and a shaper to obtain precursor 1; (B2): The precursor 1 obtained in step (B1) is subjected to a graphitization treatment at a temperature of 3000°C; (B3): The product obtained in step (B2) is put into a mechanofusion and treated at 1000 r / m for 30 minutes to obtain artificial graphite material B. This artificial graphite material B is a primary particle and has a surface roughness of 3.5.
[0154] Negative electrode plate manufacturing The artificial graphite material B, the conductive agent Super P, the adhesive SBR, and the thickener CMC-Na are mixed in a mass ratio of 96.2:0.8:1.8:1.2, and thoroughly stirred in an appropriate amount of deionized water to form a uniform negative electrode slurry. The negative electrode slurry is coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode plate is obtained. The surface density of the negative electrode film layer is 10.7 mg / cm. 2 The compaction density of the negative electrode film layer is 1.67 g / cm 3It is.
[0155] Positive electrode plate manufacturing Cathode active material LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), conductive agent (Super P), and adhesive PVDF are mixed in a weight ratio of 96.2:2.7:1.1 with an appropriate amount of NMP and thoroughly stirred to form a homogeneous positive electrode slurry. The positive electrode slurry is coated on the surface of a positive electrode current collector aluminum foil, and then dried and cold pressed to obtain a positive electrode plate. The compaction density of the positive electrode plate is 3.45 g / cm. 3 and the surface density is 18.8 mg / cm 2 It is.
[0156] Electrolyte production Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed according to a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte, where the concentration of LiPF6 is 1 mol / L.
[0157] Separator Polyethylene (PE) film is used.
[0158] Secondary battery manufacturing A positive electrode plate, a separator, and a negative electrode plate are stacked in this order and wound to obtain a battery core. The battery core is then placed in an outer casing, the above-mentioned electrolyte is added, and the resulting battery is packaged, left to stand, formed, deteriorated, and other processes, to obtain a secondary battery.
[0159] Examples 2b-17b and Comparative Examples 1b-2b Examples 2b-17b and Comparative Examples 1b-2b are basically the same as Example 1b, and the only differences are those shown in Tables 4-6. For Examples 2b-17b and Comparative Examples 1b-2b, unless otherwise specified in Tables 4-6, it indicates that they are the same as Example 1b.
[0160] The test results of the artificial graphite materials obtained in Examples 1b to 17b and Comparative Examples 1b to 2b are shown in Tables 4 to 6 below.
[0161] In Table 4, the processing method of step (B3) being "chemical" means that step (B3) is carried out by placing the material in a granulation tank, continuously passing dry air through it, raising the temperature to a predetermined processing temperature at a rate of 5°C / min, and maintaining the temperature at that processing temperature for a predetermined period of time. The processing temperature and processing time (i.e., the maintenance time) are as shown in Table 4.
[0162] In Table 4, the processing method of step (B3) being “physical” indicates that step (B3) is carried out by putting the material into the mechanofusion and processing it at a predetermined rotation speed, and the rotation speed and processing time are as shown in Table 4.
[0163] [Table 4]
[0164] [Table 5]
[0165] [Table 6]
[0166] Example 1c Negative electrode plate manufacturing The artificial graphite material A prepared in Example 1a, the artificial graphite material B prepared in Example 1b, the conductive agent Super P, the adhesive SBR, and the thickener CMC-Na are mixed in a mass ratio of 48.1:48.1:0.8:1.8:1.2, and thoroughly stirred in an appropriate amount of deionized water to form a uniform negative electrode slurry. The negative electrode slurry is coated on the surface of a negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode plate is obtained. The surface density of the negative electrode film layer is 10.7 mg / cm. 2 The compaction density of the negative electrode film layer is 1.71 g / cm 3 It is.
[0167] Positive electrode plate manufacturing Cathode active material LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), conductive agent (Super P), and adhesive PVDF are mixed in a weight ratio of 96.2:2.7:1.1 with an appropriate amount of NMP and thoroughly stirred to form a homogeneous positive electrode slurry. The positive electrode slurry is coated on the surface of a positive electrode current collector aluminum foil, and then dried and cold pressed to obtain a positive electrode plate. The compaction density of the positive electrode plate is 3.45 g / cm. 3 and the surface density is 18.8 mg / cm 2 It is.
[0168] Electrolyte production Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed according to a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte, where the concentration of LiPF6 is 1 mol / L.
[0169] Separator Polyethylene (PE) film is used.
[0170] Secondary battery manufacturing A positive electrode plate, a separator, and a negative electrode plate are stacked in that order and wound to obtain a battery core. The battery core is then placed in an outer casing, the above-mentioned electrolyte is added, and the battery is packaged, left to stand, formed, deteriorated, and other processes to obtain a secondary battery.
[0171] [Table 7] [Explanation of symbols]
[0172] Here, the explanation of the reference symbols is as follows. 1, battery pack, 2, upper casing, 3, lower casing, 4, battery module, 5, secondary battery.
Claims
1. An artificial graphite material A, the artificial graphite material A being a secondary particle, and the surface roughness η of the artificial graphite material A A (=η calculated by the following formula) is 8.5≦η A ≦12, and the true density of the artificial graphite material A is ρ A ≧2.20 g / cm 3 Artificial graphite material A. [0010] Here, SSA is the specific surface area of the artificial graphite material A, and its unit is m 2 / g, ρ is the true density of the artificial graphite material A, and its unit is g / cm 3 , n is the number of grain size intervals of the artificial graphite material A, and D k represents the average grain size of the k-th grain size section of the artificial graphite material A, and its unit is μm; V k represents the volume ratio of particles in the kth particle size interval to particles in the n particle size intervals, and its unit is %.
2. 8.5≦η A 2. The artificial graphite material A according to claim 1, wherein the Mn content is ≦10.
3. The true density of the artificial graphite material A is ρ A ≧2.25 g / cm 3 The artificial graphite material A according to claim 1 or 2,
4. Volume average particle size Dv50 of the artificial graphite material A A is Dv50 A The artificial graphite material A according to any one of claims 1 to 3, which satisfies a particle size distribution of ≧10 μm.
5. Volume average particle size Dv50 of the artificial graphite material A A 12 μm≦Dv50 A The artificial graphite material A according to claim 4, wherein the average particle size is less than or equal to 20 μm.
6. 6. The artificial graphite material A according to claim 1, wherein the specific surface area of the artificial graphite material A is 1.5-4.0 m 2 / g.
7. The artificial graphite material A according to claim 6, wherein the specific surface area of the artificial graphite material A is 2.5-3.5 m 2 / g.
8. The artificial graphite material A according to any one of claims 1 to 7, wherein the tap density of the artificial graphite material A is 0.8-1.4 g / cm 3.
9. The artificial graphite material A according to claim 8, wherein the tap density of the artificial graphite material A is 0.9-1.1 g / cm 3.
10. The artificial graphite material A according to any one of claims 1 to 9, wherein the degree of graphitization of the artificial graphite material A is 92% or more.
11. The degree of graphitization of the artificial graphite material A is 94%-97%.
12. An artificial graphite material B, the artificial graphite material B being a primary particle, and having a surface roughness η B (=η calculated by the following formula) is 4≦η B ≦5, and the true density of the artificial graphite material B is ρ B ≧2.20 g / cm 3 Artificial graphite material B. [0025] Here, SSA is the specific surface area of the artificial graphite material B, and its unit is m 2 / g, ρ is the true density of the artificial graphite material B, and its unit is g / cm 3 , n is the number of grain size intervals of the artificial graphite material B, and D k represents the average grain size of the k-th grain size section of the artificial graphite material B, the unit of which is μm, and V k represents the volume ratio of particles in the kth particle size interval to particles in the n particle size intervals, and its unit is %.
13. The true density of the artificial graphite material B is ρ B ≧2.25 g / cm 3 The artificial graphite material B according to claim 12,
14. Volume average particle size Dv50 of the artificial graphite material B B is Dv50 B The artificial graphite material B according to claim 12 or 13, which satisfies ≦15 μm.
15. Volume average particle size Dv50 of the artificial graphite material B B 5 μm≦Dv50 B The artificial graphite material B according to claim 14, having a particle size of ≦12 μm.
16. The artificial graphite material B according to any one of claims 12 to 15, wherein the specific surface area of the artificial graphite material B is 0.5 to 3.0 m 2 / g.
17. The artificial graphite material B according to claim 16, wherein the specific surface area of the artificial graphite material B is 1.0-2.5 m 2 / g.
18. The artificial graphite material B according to any one of claims 12 to 17, wherein the tap density of the artificial graphite material B is 0.8-1.4 g / cm 3.
19. The artificial graphite material B according to claim 18, wherein the tap density of the artificial graphite material B is 1.1-1.3 g / cm 3.
20. The degree of graphitization of the artificial graphite material B is 91% or more.
21. The degree of graphitization of the artificial graphite material B is 92%-94%.
22. A method for producing an artificial graphite material A, comprising the steps of: A step (A1) of providing raw materials and crushing and shaping them; A step (A2) of carrying out granulation; A step (A3) of performing a graphitization treatment; and a step (A4) of performing a surface roughening treatment to obtain the artificial graphite material A. Here, the artificial graphite material A is a secondary particle, and the surface roughness η of the artificial graphite material A is A (=η calculated by the following formula) is 8.5≦η A ≦12, and the true density of the artificial graphite material A is ρ A ≧2.20 g / cm 3 The method for producing artificial graphite material A. [0030] Here, SSA is the specific surface area of the artificial graphite material A, and its unit is m 2 / g, ρ is the true density of the artificial graphite material A, and its unit is g / cm 3 , n is the number of grain size intervals of the artificial graphite material A, and D k represents the average grain size of the k-th grain size section of the artificial graphite material A, and its unit is μm; V k represents the volume ratio of particles in the kth particle size interval to particles in the n particle size intervals, and its unit is %.
23. The method for producing artificial graphite material A according to claim 22, wherein the surface roughness of the secondary particles before the graphitization treatment is 4-6.
24. The surface roughening treatment is It involves putting the material into the Mechanofusion and processing it at a specific rotation speed. The specific rotation speed is 500-1000 rpm, The method for producing artificial graphite material A according to claim 22 or 23, wherein the treatment time is 3-60 min.
25. The specific rotation speed is 600-800 rpm, The method for producing artificial graphite material A according to claim 24, wherein the treatment time is 5-20 min.
26. The surface roughening treatment is Put the material into the granulator and keep passing dry air through it. heating to a treatment temperature and carrying out treatment at the treatment temperature; The treatment temperature is 300-800° C. The method for producing artificial graphite material A according to claim 22 or 23, wherein the treatment time is 1-8 h.
27. The treatment temperature is 400-600° C. The method for producing artificial graphite material A according to claim 26, wherein the treatment time is 2-4 h.
28. A method for producing an artificial graphite material B, comprising the steps of: A step (B1) of providing raw materials and crushing and shaping them; A step (B2) of performing a graphitization treatment; and a step (B3) of performing a surface roughening treatment to obtain the artificial graphite material B. Here, the artificial graphite material B is a primary particle, and the surface roughness η of the artificial graphite material B (=η calculated by the following formula) is 4≦η B ≦5, and the true density of the artificial graphite material B is ρ B ≧2.20 g / cm 3 The method for producing artificial graphite material B. [0045] Here, SSA is the specific surface area of the artificial graphite material B, and its unit is m 2 / g, ρ is the true density of the artificial graphite material B, and its unit is g / cm 3 , n is the number of grain size intervals of the artificial graphite material B, and D k represents the average grain size of the k-th grain size section of the artificial graphite material B, the unit of which is μm, and V k represents the volume ratio of particles in the kth particle size interval to particles in the n particle size intervals, and its unit is %.
29. The method for producing artificial graphite material B according to claim 28, wherein the surface roughness of the primary particles before the graphitization treatment is 1.5-3.
30. The surface roughening treatment is It involves putting the material into the Mechanofusion and processing it at a specific rotation speed. The specific rotation speed is 800-1000 r / m; The method for producing artificial graphite material B according to claim 28 or 29, wherein the treatment time is 20-60 min.
31. The specific rotation speed is 850-950 r / m; The method for producing artificial graphite material B according to claim 30, wherein the treatment time is 30-50 min.
32. The surface roughening treatment is Put the material into the granulator and keep passing dry air through it. heating to a treatment temperature and carrying out treatment at the treatment temperature; The treatment temperature is 300-800° C. The method for producing artificial graphite material B according to claim 28 or 29, wherein the treatment time is 1-8 h.
33. The treatment temperature is 400-600° C. The method for producing artificial graphite material B according to claim 32, wherein the treatment time is 2-4 h.
34. A secondary battery, The secondary battery includes a negative electrode plate, the negative electrode plate including a negative electrode active material, A secondary battery, wherein the negative electrode active material comprises the artificial graphite material A according to any one of claims 1 to 11 and / or the artificial graphite material B according to any one of claims 12 to 21.
35. 35. A power consuming device comprising the secondary battery of claim 34.
Citation Information
Patent Citations
Non-aqueous electrolyte secondary battery
JP2002110233A
Anode material for lithium ion secondary battery and its manufacturing method
JP2003132889A
Graphite particle, lithium ion secondary battery, negative electrode material for it, and negative electrode
JP2004134244A
Graphite material for battery electrode and method for manufacturing the same
JP2020107405A
Graphite-based negative electrode material for nonaqueous secondary battery, negative electrode for nonaqueous secondary battery, and nonaqueous secondary battery
JP2020167153A
